Navigating the Fine Line of Sustainable Tourism: A Critical Analysis with Implications for Tourism Planning - FUCHS, Kevin (Journal of Environmental Management and Tourism, 2023)
Sustainable tourism has become a hot topic due to the negative impacts of traditional tourism. The concept is designed to balance economic, social, and environmental objectives, but is complex and multifaceted. It has advantages, including the preservation of the environment and cultural heritage, and economic benefits for local communities. However, I contend that sustainable tourism also presents vast challenges such as being difficult to define and measure, being more expensive than traditional forms of tourism (in part), and potentially having negative impacts on local communities. Another major challenge is the lack of incentives for industry players, which makes it hard for stakeholders to embrace sustainable tourism methods and practices. The article concludes that governments must prioritize sustainable tourism initiatives and provide adequate resources and support to ensure their successful implementation.